Empowering career decision-making: a practical strategy for using occupational information. - Geyer, Paul D.; Johnson, Virginia Anne; Hunter, John E. (Journal of Rehabilitation)
The Dictionary of Occupational Titles (DOT, 1977) has long provided rehabilitation professionals with the best available information of its kind to use in critical rehabilitation activities. Uniquely comprehensive and easy to access, this widely used resource does not offer perfectly reliable occupational information. The increased need for occupational information created by changes in the labor market makes the DOT too valuable a resource to ignore or underutilize because of concerns about reliability. This paper presents a strategy designed to maximize user confidence in utilizing DOT information. Reprinted by permission of the publisher.